1999
DOI: 10.1002/j.2161-0045.1999.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual Review: Practice and Research in Career Counseling and Development—1998

Abstract: The article reviews the practice and research literature in career counseling and development in 1998. The literature is presented and discussed under the following topical headings: contexts and populations, career processes, transitions, career assessment, and career counseling, services and programs.The career counseling and development literature published in 1998 was diverse and extensive. To reflect this diversity, we have selected pertinent articles from the leading journals in the field of career couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 252 publications
0
17
0
1
Order By: Relevance
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…For most of that time, the emphasis has been on quantitative assessment which is evidenced in consecutive annual reviews of practice and research in career counselling and development published in the journal, The Career Development Quarterly (e.g., Arbona, 2000;Luzzo & MacGregor, 2001;Young & Chen, 1999), where qualitative career assessment is seldom, if at all, mentioned and then only briefly. Career development practitioners have been slow to move from this traditional position with its emphasis on quantitative assessment (Brown & Brooks, 1996).…”
Section: Assessment In Career Counsellingmentioning
confidence: 99%
“…Unfortunately, most programs have tended to focus on specific skills and skill-building interventions and have ignored the psychological variables that have been associated with career development and vocational behavior (Strauser, 1996). One variable that has received attention in the career development literature has been career decision-making cognitions and the potential impact of negative cognitions on vocational development (Luzzo, Hitchings, Retish, & Shoemaker, 1999;Young & Chen, 1999). Research focusing on career decision making has suggested that cognitions can affect career behavior in the following ways: Individual career behaviors can be viewed as responses to the individual's cognitive conceptualizations of career environments; learning and cognitive development can modify the individual's career representations; cognitions, behaviors, and environments interact to influence vocational behavior; and cognitions mediate changes in career behaviors (Keller, Biggs, & Gysbers, 1982;Peterson, Sampson, & Reardon, 1991;Sampson, Peterson, Lenz, Reardon, & Saunders, 1996).…”
mentioning
confidence: 99%
“…With an individual's cognitions playing such a significant role in the career development process, it is important for individuals to have healthy and appropriate career thoughts and to minimize the amount of dysfunctional career thoughts (Young & Chen, 1999). Dysfunctional career thoughts usually revolve around issues of self-worth, perfectionism, and overgeneralization; such thoughts tend to decrease an individual's overall life satisfaction (Sampson et al, 1996).…”
mentioning
confidence: 99%